1986
DOI: 10.1056/nejm198605223142101
|View full text |Cite
|
Sign up to set email alerts
|

Responses to Corticotropin-Releasing Hormone in the Hypercortisolism of Depression and Cushing's Disease

Abstract: Primary depression can be associated with substantial hypercortisolism, thus prompting some researchers to suggest that depression shares pathophysiologic features with Cushing's disease. Clinically, depression can be difficult or impossible to distinguish from mild or early Cushing's disease that is associated with depressive features. The purpose of this study was to evaluate whether the pituitary-adrenal responses to ovine corticotropin-releasing hormone could help to clarify the mechanism of hypercortisoli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
203
3
5

Year Published

1987
1987
2006
2006

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 758 publications
(228 citation statements)
references
References 45 publications
17
203
3
5
Order By: Relevance
“…Similar to findings in animal models of ELS, depressed patients show increased CSF CRF concentrations (Nemeroff et al, 1984) as well as increased CRF mRNA expression and CRF concentrations in the hypothalamic PVN and the locus coeruleus (Raadsheer et al, 1994(Raadsheer et al, , 1995Bissette et al, 2003). Blunted ACTH responses to CRF stimulation provide indirect evidence for CRF hypersecretion in patients with depression (Holsboer et al, 1984;Gold et al, 1986) and parallel findings of blunted responses in abused women with depression and findings of downregulated pituitary CRF receptors in maternally separated rats. Escape from cortisol suppression in the combined dexamethasone/CRH test, as recently observed in humans in relation to ELS, is believed to be the most sensitive marker for HPA axis dysfunction in major depression and also detects vulnerability to depression in first-degree relatives of depressed patients (Holsboer et al, 1995).…”
Section: Comparison Of the Neurobiology Of Els And Depressionmentioning
confidence: 78%
“…Similar to findings in animal models of ELS, depressed patients show increased CSF CRF concentrations (Nemeroff et al, 1984) as well as increased CRF mRNA expression and CRF concentrations in the hypothalamic PVN and the locus coeruleus (Raadsheer et al, 1994(Raadsheer et al, , 1995Bissette et al, 2003). Blunted ACTH responses to CRF stimulation provide indirect evidence for CRF hypersecretion in patients with depression (Holsboer et al, 1984;Gold et al, 1986) and parallel findings of blunted responses in abused women with depression and findings of downregulated pituitary CRF receptors in maternally separated rats. Escape from cortisol suppression in the combined dexamethasone/CRH test, as recently observed in humans in relation to ELS, is believed to be the most sensitive marker for HPA axis dysfunction in major depression and also detects vulnerability to depression in first-degree relatives of depressed patients (Holsboer et al, 1995).…”
Section: Comparison Of the Neurobiology Of Els And Depressionmentioning
confidence: 78%
“…The evidence for the specificity, and clinical and biological plausibility of endophenotypes related to dysfunctions of the hypothalamic and extrahypothalamic CRH system for MDD is abundant: Levels of CRH in the CSF are elevated in some depressed subjects (Nemeroff et al, 1984), while the pituitary response to CRH appears appropriate given the high cortisol levels (Gold et al, 1986); the number of CRHsecreting neurons in limbic brain regions is increased (Raadsheer et al, 1994); the number of CRH binding sites in the frontal cortex is reduced, possibly as a compensatory response to increased CRH concentrations (Nemeroff et al, 1988); CRH produces a number of physiological and behavioral alterations that resemble the symptoms of major depression including decreased appetite, disrupted sleep, decreased libido, and psychomotor alterations (Nemeroff, 1996); and anxiety and depression scores have been reduced following CRH-1 receptor blockade (Zobel et al, 2000).…”
Section: Hpa Axis and Crhmentioning
confidence: 99%
“…[20][21][22] This blunted ACTH response could be caused by the downregulation of pituitary CRH receptors due to chronic hypersecretion in depressed persons. 23 This hypothesis correlates with findings in post-mortem studies on suicide victims that have revealed decreased CRH receptor density in the frontal cortex.…”
Section: Hpa Axis Dysregulation In Obesity and Depressionmentioning
confidence: 99%